2015
DOI: 10.1209/0295-5075/111/38003
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-based coarse-graining of evolved dynamical networks

Abstract: -Networks with a prescribed power-law scaling in the spectrum of the graph Laplacian can be generated by evolutionary optimization. The Laplacian spectrum encodes the dynamical behavior of many important processes. Here, the networks are evolved to exhibit subdiffusive dynamics. Under the additional constraint of degree-regularity, the evolved networks display an abundance of symmetric motifs arranged into loops and long linear segments. Exploiting results from algebraic graph theory on symmetric networks, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…To facilitate dissemination, we provide full implementations of all the algorithms described in this article 26 . Our results supersede 11,13 and help to understand other network symmetry results thereafter 12,[27][28][29][30][31] . We focus on structural and spectral properties, and symmetries commonly found in real-world networks: For a more general study of arbitrary symmetry in (networks of) dynamical systems, see refs.…”
supporting
confidence: 68%
“…To facilitate dissemination, we provide full implementations of all the algorithms described in this article 26 . Our results supersede 11,13 and help to understand other network symmetry results thereafter 12,[27][28][29][30][31] . We focus on structural and spectral properties, and symmetries commonly found in real-world networks: For a more general study of arbitrary symmetry in (networks of) dynamical systems, see refs.…”
supporting
confidence: 68%
“…Finally, we remark that at this point we cannot answer the question why the observed core-periphery structures generate the power-law Laplacian spectra and, thus, anomalous diffusion behavior. In a different settingwhere evolving networks were kept homogeneous-it was observed that networks with loops and dangling ends of different lengths are also able to generate such behavior [35]. A distribution of paths of different lengths through the network might as well be generated by the core-periphery structures found here.…”
Section: Discussionmentioning
confidence: 65%
“…In both cases the integrated spectral densities display several kink-like features which reflect accumulations of eigenvalues. A possible mechanism underlying such spectral degeneracies are network symmetries [35]. These features are absent from the spectra obtained using the Co and Co-Cl algorithms, which both resemble the target power law closely and almost equally well.…”
Section: Reconstruction Using Partial Informationmentioning
confidence: 94%
“…While this is not by itself a deterrent to the application of Decimateas it only needs to be used once on a systemthere is definitely room for improvement. For symmetric systems such as viral capsids, their symmetric organization may provide simplification . More generic systems require aggressive optimizations of the current implementation of Decimate.…”
Section: Discussionmentioning
confidence: 99%
“…For symmetric systems such as viral capsids, their symmetric organization may provide simplification. 76 More generic systems require aggressive optimizations of the current implementation of Decimate. We reserve those improvements for future studies.…”
Section: Discussionmentioning
confidence: 99%